WASTEWATER IRRIGATION SAFETY AND HEAVY METAL CONTAMINATION AWARENESS OF FARMERS ALONG JAKARA RIVER KANO, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
The water in the Jakara River consists of effluent from Bompai industries, domestic sewage from most parts of Kano city and runoffs from various local scraps and chemical processing. The wastewater in the river is the main and most preferred source of irrigation water for the farmers along the Jakara River. The wastewater in the river is rich in both organic and chemical contaminants that can contaminate soil and thriving crops. The research was designed to understand the perception of farmers about the safety of the irrigation water they use and its resulting consequences on soil quality and food safety. The information on the farmer’s awareness were gathered through oral interviews, 60 farmers were selected for data collection. Information collected includes the demography of the farmers, their farming experience, their concern about the safety of wastewater irrigation and awareness of the dangers associated with soil and food heavy metals (HMs) contamination. The majority (95 %) of the farmers ignorantly believe that the wastewater in the Jakara River is safe for irrigation and 90.00 % believe that crops cannot be contaminated when irrigated with contaminated wastewater. Only 5 % of the farmers know HMs and more than 86 % believe that even if the water is contaminated it cannot pass contamination to soil and growing crops. The overall farmers' awareness of the safety of wastewater irrigation and soil and crop HM contamination is generally poor.
Keywords: Contamination; Heavy metals; Irrigation; Jakara river; Wastewater